IPM system in agriculture / v.1. Principles and perspectives - Upadhyay, R. K., 1953-; Mukerji, K. G.; Rajak, R. L.; Dubey, O. P. (New Delhi : Aditya Books, 1996)
With reference to India.
v.1. Principles and perspectives -- v. 2. Biocontrol in emerging biotechnology -- v. 3. Cereals -- v. 4. Pulses -- v. 5. Oilseeds -- v. 6. Cash crops -- v. 7. Key animal pests
Vol. 6-<7 > edited by Rajeev K. Upadhyay, K.G. Mukerji, O.P. Dubey.
Includes bibliographical references and index.
Keywords: Agricultural pests -- Integrated control -- India; Grain -- Diseases and pests -- Control -- India; Seed crops -- Diseases and pests -- Control -- India; Oilseed plants -- Diseases and pests -- Control -- India; Agricultural pests -- Integrated control -- Environmental aspects